Neurotoxicity evoked by organophosphates and available countermeasures - Pulkrabkova, Lenka; Svobodova, Barbora; Konecny, Jan; Kobrlova, Tereza; Muckova, Lubica; Janousek, Jiri; Pejchal, Jaroslav; Korabecny, Jan; Soukup, Ondrej (Archives of toxicology, 2023)
Organophosphorus compounds (OP) are a constant problem, both in the military and in the civilian field, not only in the form of acute poisoning but also for their long-lasting consequences. No antidote has been found that satisfactorily protects against the toxic effects of organophosphates. Likewise, there is no universal cure to avert damage after poisoning. The key mechanism of organophosphate toxicity is the inhibition of acetylcholinesterase. The overstimulation of nicotinic or muscarinic receptors by accumulated acetylcholine on a synaptic cleft leads to activation of the glutamatergic system and the development of seizures. Further consequences include generation of reactive oxygen species (ROS), neuroinflammation, and the formation of various other neuropathologists. In this review, we present neuroprotection strategies which can slow down the secondary nerve cell damage and alleviate neurological and neuropsychiatric disturbance. In our opinion, there is no unequivocal approach to ensure neuroprotection, however, sooner the neurotoxicity pathway is targeted, the better the results which can be expected. It seems crucial to target the key propagation pathways, i.e., to block cholinergic and, foremostly, glutamatergic cascades. Currently, the privileged approach oriented to stimulating GABAAR by benzodiazepines is of limited efficacy, so that antagonizing the hyperactivity of the glutamatergic system could provide an even more efficacious approach for terminating OP-induced seizures and protecting the brain from permanent damage. Encouraging results have been reported for tezampanel, an antagonist of GluK1 kainate and AMPA receptors, especially in combination with caramiphen, an anticholinergic and anti-glutamatergic agent. On the other hand, targeting ROS by antioxidants cannot or already developed neuroinflammation does not seem to be very productive as other processes are also involved.
Keywords: Organophosphate Poisoning; záchvaty; Acetylcholinesterase; cholinesterasové inhibitory; acetylcholinesterasa; reaktivní formy kyslíku; Neurotoxicity; Cholinesterase Inhibitors; Neurotoxicity Syndromes; Seizures; Neuroinflammatory Diseases; organofosfáty; otrava organofosfáty; Neuroprotection; Reactive Oxygen Species; neurotoxické syndromy; Humans; Organophosphates; lidé; neurozánětlivé nemoci